2002
DOI: 10.1017/s0021859602002290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spray application of urea fertilizer at stem extension on winter wheat yield

Abstract: Supplying a proportion of the N requirement of a wheat crop via the foliage would potentially reduce immobilization of fertilizer N in the soil organic matter and N losses by leaching or denitrification. A field experiment was carried out at Harper Adams in Shropshire to investigate the effect on crop yield of supplying the spring N application to winter wheat as different proportions of urea as a solution rather than as conventional soil-applied urea, and to determine the physiological basis of any yield diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
2
2
0
1
Order By: Relevance
“…However, damage of the flag leaf tips seems to be well tolerated by wheat, as confirmed by the appreciable yield and grain quality improvements reached by all foliar treatments, regardless of the fertilizer choice between UAN and urea. This is in agreement with the findings of several authors [11,24,26], while other studies [15,30] reported a higher threshold, i.e., 40 kg ha −1 as a single application between stages ZDS 39 (flag leaf visible) and ZDS 73 (early milk development), without compromising productivity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, damage of the flag leaf tips seems to be well tolerated by wheat, as confirmed by the appreciable yield and grain quality improvements reached by all foliar treatments, regardless of the fertilizer choice between UAN and urea. This is in agreement with the findings of several authors [11,24,26], while other studies [15,30] reported a higher threshold, i.e., 40 kg ha −1 as a single application between stages ZDS 39 (flag leaf visible) and ZDS 73 (early milk development), without compromising productivity.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, many agronomic parameters, such as yield, harvest index and TSW, were preserved under low N doses supplied by foliar spraying, suggesting that this approach to fertilization in wheat is feasible, as indicated by the previous literature [24,31]. Our experimental soil had a relatively good fertility, with 0.11% N and 1.7% organic matter, which could have prevented a correct evaluation of N shortage compared to common practice.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These workers deposit faecal droplets from rectal sac fluids and deposit them throughout their territory (Dejean & Beugnon, ; Offenberg, ), especially on flushing leaves and developing fruits, where ant activity is highest (Hölldobler & Wilson, ; Offenberg, Nielsen, Macintosh, Aksornkoae, & Havanon, ). These faecal droplets contains nutritious compounds such as amino acids and urea (Vidkjær, Wollenweber, Gislum, Jensen, & Fomsgaard, ; Vidkjær et al., ), compounds that are commonly used as foliar fertilisers in agriculture, as they can be absorbed directly by plant leaves (Abad, Lloveras, & Michelena, ; Readman, Kettlewell, & Beckwith, ; Varga & Svečnjak, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nesses trabalhos, constatou-se que a resposta das cultivares de trigo a irrigação e fertilização, é caraterizada pela relação positiva entre tais fatores. A natureza desta interação, entretanto, é função das condições edafoclimáticas, cultivares e técnicas de manejo empregadas (Frizzone et al, 1996;Sandhu et al, 2002;Readman et al, 2002). A eficiência e/ou resposta dos genótipos de trigo a doses de nitrogênio em relação à produtividade, depende da disponibilidade de água.…”
Section: Introductionunclassified